Combining ability analysis in Indian mustard (Brassica juncea L. Czern and Coss.): COMBINING ABILITY IN INDIAN MUSTARD - H P MEENA; H KUMAR; J P LAL (Journal of Oilseeds Research, 2013)
A line x tester analysisinvolving five males(lines) and 10 female (testers) parents were carried out for five traits in Indian mustard. (Brassica juncea L. Czern & Coss.). Among the parents, MCN-75, Ornamental Rai, Rohini, Kranti, Vardan, RH-8812, and NDR-8501 were found to be significantly superior general combiners for seed yield and yield components. The cross MCN-75 x Rohini, MCN-75 x NDR-8501, MCN-75 x Vardan and MCN-73 x Krantishowed high heterosisforseed yield and some ofthe yield contributing traits. The cross MCN-75 x RH-8812, MCN-73 x Pusa Bold, Ornamental Rai x NDR-8501 and MCN-70 x RH-8813 had higher sca effects. For most of the major characters including seed yield both additive and non-additive gene action were of prime importance.